Sequences and Series - Mahmudov, E. (Atlantis Press, 2013)
In this chapter we give the basic properties of monotone, strictly monotone, and Cauchy sequences in detail. In particular, we treat the convergence tests of Cauchy, D’Alembert, Leibniz, and Raabe. As examples, we consider the harmonic series, the geometric series, and products of series.